1993
DOI: 10.1172/jci116458
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mutant and normal beta T3 receptor alleles in kindreds with generalized resistance to thyroid hormone.

Abstract: Thyroid hormone resistance (THR) is primarily an autosomal dominant inherited disease characterized by resistance of pituitary and peripheral tissues to the action of thyroid hormone. We investigated whether the heterogeneous phenotypic features that occur not only among kindreds but also within the same kindred might be due to the expression of differing ratios of mutant and normal receptors in tissues. Using an allele-specific primer extension method, we determined the relative expression of normal and mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The only two studies that address this issue reported conflicting results (28,29). In the first study, the severity of growth delay in a kindred with RTH correlated with the increased ratio of mutant to wild-type TR␤1 mRNA in fibroblasts (28). However, in a second study, no correlation was found between the relative ratios of mutant and normal TR␤1 mRNA in fibroblasts and the clinical phenotype of RTH patients (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only two studies that address this issue reported conflicting results (28,29). In the first study, the severity of growth delay in a kindred with RTH correlated with the increased ratio of mutant to wild-type TR␤1 mRNA in fibroblasts (28). However, in a second study, no correlation was found between the relative ratios of mutant and normal TR␤1 mRNA in fibroblasts and the clinical phenotype of RTH patients (29).…”
Section: Discussionmentioning
confidence: 99%
“…One of the unresolved issues in understanding the molecular basis of RTH has related to the relative levels of mutant to wild-type TR␤1 protein to produce a clinical phenotype in different organs. The only two studies that address this issue reported conflicting results (28,29). In the first study, the severity of growth delay in a kindred with RTH correlated with the increased ratio of mutant to wild-type TR␤1 mRNA in fibroblasts (28).…”
Section: Discussionmentioning
confidence: 99%
“…This phenotypic variation can occur across families [38] and within the same family [57]. Finding differences in the relative expression level of the mutant relative to the normal TRβ allele has not been consistent [48,58]. Genetic variability of factors other than TRβ may modulate the phenotype of RTH.…”
Section: Variants Above)mentioning
confidence: 99%
“…The inhibitory effect of T4 on cardiac collagen synthesis has been observed in rat, mouse and dog (Edgren et al 1976, Bonnin et al 1983, Yao & Eghbali 1992a,b, Kim et al 1996, Klein et al 1996, and it has been postulated that this negatively affects the supporting properties of the myocardial connective tissue (Edgren et al 1976). Fibroblasts from human skin biopsies express a thyroid hormone receptor (Mixson et al 1993), and it is possible that, besides the well-investigated collagen genes, novel thyroid hormone-responsive genes will be identified in (cardiac) fibroblasts. Indeed, the recently discovered ZAKI-4 gene, with an as yet unknown function, was identified in fibroblasts and found to be transcribed in heart and several other organs (Miyazaki et al 1996a,b).…”
Section: Introductionmentioning
confidence: 99%